MIGRATION INHIBITION ACTIVITY BY METHANOL EXTRACT Hibiscus tiliaceus Linn. ON 4T1 BREAST CANCER - Alviani, Dwi Lutvi; Safitri, Erika Indah; Hidayati, Devi Nisa (Universitas Muhammadiyah Magelang, 2024)
The prevalence of breast cancer cases in Indonesia is increasing along with the ability of cancer cells to migrate or move from the primary tumor mass and form new colonies elsewhere. The migration of cancer cells has encouraged the develop anticancer drugs from natural ingredients. Waru leaves have been shown to have cytotoxic activity. This study aims to determine the inhibition activity of migration of breast cancer cells 4T1 from methanol extract of waru leaves. Waru leaves methanol extract was obtained using the maceration method. Cytotoxic test of methanol extract of waru leaves (MEWL) was the migration test used in the scratch wound healing method at concentrations 162.5, 325, and 650 μg/mL at 0, 18, 24, and 42 hours after treatment. Analysis of IC50 using linear regression, while large areas were analyzed using Image-J software. The percentage of data closure was analyzed statistically with the Anova Repeated Measure test. All concentrations of Methanol Extract of Waru Leaves had significant inhibition of cell migration (p<0,05) compared to control at each observation time at 0, 18, 24, and 42 hours after treatment. So, MEWL is able to inhibit migration in 4T1 cells